1998
DOI: 10.1021/jp982161j
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of 1,2-Dimethoxyethane/Water Solutions. 2. Dynamical Properties

Abstract: We have performed molecular dynamics simulations of 1,2-dimethoxyethane (DME)/water solutions at 318 K in order to examine conformational, translational, and rotational dynamics of the solutions as a function of composition. The rate of conformational transitions for the C-O;C-C and the O-C;C-O dihedrals in DME decreases with increasing water content for mole fraction X DME g 0.18. For more dilute solutions, the conformational transition rate is independent of composition. Self-diffusion coefficients of DME an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 19 publications
6
31
0
Order By: Relevance
“…(17) (18) Eliminating F from Eq. (18) as before produces the ratio (19) As mentioned earlier, the gas phase dipole moment is ; hence, the static, low frequency bulk dielectric constant ε 0 is related to the molecular electrical polarizability and the dipole moment of the molecules through, (20) Combining the two equations (19) and (20) to eliminate α yields . Introducing this relationship into Eq.…”
Section: General Expression For Self-energy Of a Chargementioning
confidence: 94%
See 2 more Smart Citations
“…(17) (18) Eliminating F from Eq. (18) as before produces the ratio (19) As mentioned earlier, the gas phase dipole moment is ; hence, the static, low frequency bulk dielectric constant ε 0 is related to the molecular electrical polarizability and the dipole moment of the molecules through, (20) Combining the two equations (19) and (20) to eliminate α yields . Introducing this relationship into Eq.…”
Section: General Expression For Self-energy Of a Chargementioning
confidence: 94%
“…The PEO/water system has been extensively studied by Smith and coworkers with molecular dynamics simulations. 20 The use of an implicit solvent model would reduce the computational cost of simulating the dynamic and equilibrium properties of PEO by at least two orders of magnitude and would facilitate the study of more complex systems. As a first step towards developing an implicit solvent model for describing the structure and dynamics of PEO in aqueous solutions, we consider its building block, namely DME, the shortest ether molecule that reproduces the local conformations of PEO.…”
Section: Application To Conformational Populations Of 12: Dimetmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that the Debye theory of rotational relaxation is application [50], the rotational correlation times (t) are inversely proportional to rotational diffusion coefficient. From Fig.…”
Section: Kinetic Analysismentioning
confidence: 99%
“…The electrostatic interaction energy components were subtracted from the total binding energies by the Coulomb potential using the partial changes on PEG and water molecules shown in Table 3.2 and 3.8. The remaining binding energy components were fitted to the LJ potential using least square fitting method to obtain the LJ parameters [69,70,68]. In order to verify the interaction parameters between PEG and water, we simulated a system composed only of DME chains and water (the mole fraction of DME is 0.04) and calculated the radial distribution function of the oxygen of the DME with the oxygen of water and obtained good agreement with the results of Borodin et al [68], as shown in Figure 3.4.…”
Section: Force Field Parameters For Interactions Between Peg and Watermentioning
confidence: 99%